2016
DOI: 10.1002/bjs.10192
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the endovenous revolution

Abstract: Not as cost‐effective as you might think

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…1e4 The report of Hamann et al strongly supports fears presented in a leading article in the British Journal of Surgery in 2016. 5 The 5 year results show that open surgery generates less groin recurrence than laser and foam, and matches laser treatment results in other areas. This was clearly pointed out by the authors, but they failed to draw conclusions from what were for many, unexpected results.…”
supporting
confidence: 61%
“…1e4 The report of Hamann et al strongly supports fears presented in a leading article in the British Journal of Surgery in 2016. 5 The 5 year results show that open surgery generates less groin recurrence than laser and foam, and matches laser treatment results in other areas. This was clearly pointed out by the authors, but they failed to draw conclusions from what were for many, unexpected results.…”
supporting
confidence: 61%
“…Recently, in Europe, data suggesting that side-branch regurgitation from the SFJ stump left following HT+S or EVA resulted in a significantly higher rate of symptomatic REVAS than Neo. 17 – 19 ) There are reports in immunohistological studies 20 ) denying Neo as a neovascularization. The other report demonstrated that it is a mere innocent bystander unrelated to REVAS.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the clinical risk for early groin recurrence and especially neovascularization seems to have been overestimated or could have been the result of inadequate open surgical technique used in some RCTs [8,9]. These findings have also been confirmed by long term follow-up from several RCTs, included in systematic reviews and meta-analyses, that show more groin recurrence long term from endovenous techniques than from open surgery [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…That re-do surgery leads to inferior results has been clearly shown underlining that it is extremely important to avoid recurrent varicose veins by performing a thorough primary intervention [13]. The most important measure is not to leave SFJ stumps behind, which is probably the reason for the higher numbers of groin recurrences long term from endovenous ablations in RCTs [10][11][12]. By employing a safety margin of 1-2 cm to avoid EHIT the result is in most cases a stump left behind, often connecting to tributaries and most often the anterior accessory saphenous vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation